Cerebellar hemorrhage: a 10-year evaluation of risk factors. (1st November 2020) - Vesoulis, Zachary A.; Herco, Maja; El Ters, Nathalie M.; Whitehead, Halana V.; Mathur, Amit
Abstract: Background: While cerebellar hemorrhage (CH) has been linked with adverse neurodevelopmental outcome in preterm infants, it remains under-recognized and the underlying mechanisms are not fully understood. Objective: To determine risk factors for CH in premature infants. Methods: A retrospective cohort study included all inborn infants ≤ 30 weeks EGA admitted to the NICU from 2007 to 2016. Comprehensive perinatal and clinical factors were collected. CH size, sidedness, and symmetry were noted. Factors associated with CH were evaluated using univariate and multivariate logistic regression. Results: Of the 352 identified infants, 69 (20%) had CH. Those with CH were born at earlier EGA, received less antenatal steroids, more frequently had an admission temperature <36 °C, had more severe lung disease, received more inotropes, and had higher rates of intraventricular hemorrhage (IVH). In the regression model, low admission temperature (OR = 3.5), inotrope exposure (OR = 2.6), chorioamnionitis (OR = 2.3), and increased ventilator days (OR = 1.02) were associated with increased risk, while antenatal steroids (OR = 0.3) and male sex (OR = 0.5) were associated with decreased risk. Imaging modality at first diagnosis was split between ultrasound and MRI (52 versus 48%). Median age at diagnosis was 4 d; 52% of cases were unilateral, and size was punctate, small, and large in 23, 45, and 32% of cases, respectively. Conclusions: CH is common in premature infants and can be diagnosed using ultrasound or MRI. Clinically modifiable risk factors have been identified and should serve as the basis for improved clinical strategies in temperature, ventilator, and blood pressure management.